Scaling Up of Nature-Based Solutions to Guide Climate Adaptation Planning: Evidence From Two Case Studies - Cilliers, Elizelle Juanee; Timmermans, Wim; Rohr, Hildegard; Goosen, Hasse (Frontiers in Sustainable Cities, 2022)
Nature-based solutions are gaining importance within the notion of urban sustainability problems and associated global goals. This paper argues that nature-based solutions could guide climate adaptation planning, but it would need to be scaled-up across the globe to have an effective impact on climate adaptation. Literature poses various proposals of how to include nature-based solutions to guide adaptation planning, but practical examples and evidence of such are more limited. This paper addresses this lack by providing examples of two case studies, one in the Netherlands (Amersfoort) and one in South Africa (Lephalale). These two case studies were purposefully selected based on the nature-based approaches they employed in response to climate change challenges. The cases were accordingly considered in terms of their socio-ecological and environmental context, the scale of implementation of the nature-based solutions, the flexibility of these responses employed, and the overall benefits provided through the nature-based approaches. A comparative analysis was conducted between the two cases and highlighted that nature-based approaches could not be limited to a singular ad-hoc approach, but should rather be scaled up and more comprehensive, in order to align with the objectives of climate adaptation planning. The cases evidenced how the broader environment could benefit when nature-based solutions are scaled up to guide climate adaptation.